Constructor de áreas y perímetros - Agüero-Calvo, Evelyn (My University, 2021)
En este taller se les presenta una aplicación interactiva elaborada por la Universidad de Colorado, gratuita y de uso libre, que se ejecuta directamente en el navegador. También se puede descargar y enviar el archivo. Link: https://phet.colorado.edu/sims/html/area-builder/latest/area-builder_es.html

In this workshop, they are presented with an interactive application developed by the University of Colorado, free and open to use, which runs directly in the browser. You can also download and send the file. Link: https://phet.colorado.edu/sims/html/area-builder/latest/area-builder_es.html
Keywords: Aplicaciones interactivas; Cálculo -- Áreas; Cálculo -- Perímetro; Geometría; Matemáticas; Interactive applications; Calculus -- Areas; Calculus -- Perimeter; Geometry; Mathematics